Labor Dispute Mediation: A Constitutional Perspective to Realize Social Justice in the 1945 Constitution - Riana, Ana; Enrico Winadi; Riski Eka Purnairawan (Universitas Islam Negeri Raden Intan Lampung, 2026)
This study aims to analyze labor dispute mediation as a constitutional vehicle for realizing social justice, not merely an administrative instrument. The urgency of this study departs from the fact that the settlement of labor disputes through mediation in Indonesia has so far been more emphasized on procedural efficiency and technical neutrality, without considering the structural inequality between workers and employers, so that substantive justice as mandated by the Preamble and Article 27 paragraph (2) of the 1945 Constitution of the Republic of Indonesia is often ignored. The research adopts a normative juridical approach, examining primary legal materials (the 1945 Constitution and Law No. 2 of 2004 concerning the Settlement of Industrial Relations Disputes) and secondary legal materials through literature studies and content analysis. The results show that the prevailing mediation framework tends to prioritize speed and formality, potentially giving rise to a